1195 EFFECTIVENESS OF A NEW PROACTIVE MULTIDISCIPLINARY CARE SERVICE FOR OLDER PEOPLE WITH FRAILTY: A NON-RANDOMISED CONTROLLED TRIAL. (16th January 2023) - Murtagh, F E M; Okoeki, M; Ukoha-kalu, B O; Khamis, A; Clark, J; Boland, J W; Pask, S; Nwulu, U; Elliott-Button, H; Folwell, A; Johnson, M J; Harman, D
Abstract: Introduction: Integrated care potentially improves health outcomes for older people with frailty. We aimed to assess the effectiveness of a new, proactive, multidisciplinary care service in improving the wellbeing and quality-of-life of older people with frailty. Methods: A community-based non-randomised controlled trial. Participants (≥65 years, electronic Frailty Index ≥0.36) received either this new integrated care service plus usual care, or usual care alone. Data collection was at 3 time points: baseline, 2-4 weeks, and 10-14 weeks; the primary outcome was patient well-being at 2-4 weeks, measured using the Integrated Patient Outcome scale, IPOS. The secondary outcome was quality-of-life, measured using EQ-5D. Wellbeing and quality-of-life at 10-14 weeks were measured to test safety and duration of effect. Data was analysed with STATA v17. Results: 199 intervention and 54 control participants were recruited. At baseline, participants were similar in age/gender/body mass index/ethnicity/living status. At 2-4 weeks, the intervention group had improved well-being (median IPOS reduction 5, versus control group increase 2, p<0.001) and improved quality of life (median EQ-5D index values increase 0.12, versus control 0.00, p<0.001); these were clinically significant. After adjusting for age, gender and living status, intervention group had an average total IPOS score reduction of 6.34 (95% CI: -9.01: -4.26, p<0.05). Propensity score matching analysis based on functional status/deprivation score showed similar results (reduction in IPOS score in intervention group 7.88 (95% CI: -12.80: -2.96, p<0.001). At 10-14 weeks, the intervention group sustained well-being improvement (median IPOS score reduction 4, versus control increase 2, p<0.001) and improved quality of life (median EQ-5D index values increase 0.06, versus control -0.01, p<0.001). Conclusion: This new integrated care service improves the overall wellbeing and quality of life of older people with frailty at 2-4 weeks; improvement was sustained at 3 months. Ethics Approval: IRAS-250981 and NHS Research Ethics Committee 18/YH/0470.